Utilization of Google Workspace as a Productivity and Collaborative tool in supporting Active, Innovative, and Creative Learning at SMAN 3 Parepare - Alvian Tri Putra DA; Rosmiati Rosmiati; Khaera Tunnisa; Maratuttahirah Maratuttahirah; Rakhmadi Rahman; Noel Ivander Pusung; Danang Fatkhur Razak; Nur Fadillah Hakim; Siti Nurhalizah; Syafira Fatwa; Alya Wulan Apriliyani (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Community service activities that will be carried out at SMAN 3 Parepare are community service activities that will be carried out based on problems in partner schools, namely in the teaching and learning process where teachers provide material and assignments by explaining directly to students without any media and learning technology. A learning process like this can reduce student enthusiasm for learning, so learning objectives cannot be adequately achieved. The purpose of this service activity is to provide an introduction and training to teachers and students regarding Google Workspace for Education, which has advantages such as having virtual classes, online absences, implementing online video streaming/face-to-face learning, being able to assess student assignments directly, availability of facilities which can assist students and teachers in terms of uploading and downloading lesson materials and projects, providing discussion forum facilities, as a simple and flexible tool to increase the effectiveness of collaboration between teachers and students and as a comprehensive solution in the use of technology for teachers to be able to develop professionally, work efficiently, teaching interactively by utilizing Google Workspace for Education for learning, and being able to increase student learning enthusiasm to encourage academic integrity to support active, innovative and creative learning.